Unimaginable atrocities justice, politics, and rights at the war crimes tribunals - Schabas, William, 1950- (Oxford : Oxford University Press, 2012)
As international criminal justice has grown in prominence, so have the challenges facing it. This text discusses the unresolved questions and dilemmas confronted by international war crimes courts, including the controversies surrounding prosecutorial policy, the tension between peace and justice, and accusations of victor's justice.
Includes bibliographical references and index.
Description based on print version record.
Keywords: War crime trials; Trials (Crimes against humanity); International criminal courts; International criminal law